2003
DOI: 10.1079/nrr200357
|View full text |Cite
|
Sign up to set email alerts
|

Physiological factors that regulate the use of endogenous fat and carbohydrate fuels during endurance exercise

Abstract: Exercise causes a dramatic increase in energy requirements because of the metabolic needs of working muscles. Exercise-dependent factors regulate fuel use. Absolute exercise intensity determines the exercise-induced increase in energy demands, whereas exercise intensity relative to an individual's maximal aerobic capacity (VO 2 max) determines the proportional contribution of different fuel sources (i.e. plasma glucose, plasma fatty acids, muscle glycogen and intramuscular triacylglycerols). Endurance training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 178 publications
(251 reference statements)
0
10
0
Order By: Relevance
“…Evaluating lipid kinetics in men and women during exercise is particularly difficult because it is affected by body composition, aerobic fitness, and training status, age, menstrual cycle phase (during high-intensity exercise), and possible other less explored factors such as muscle fiber-type composition (24,25). This may explain in part the often controversial results in the literature.…”
Section: Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…Evaluating lipid kinetics in men and women during exercise is particularly difficult because it is affected by body composition, aerobic fitness, and training status, age, menstrual cycle phase (during high-intensity exercise), and possible other less explored factors such as muscle fiber-type composition (24,25). This may explain in part the often controversial results in the literature.…”
Section: Exercisementioning
confidence: 99%
“…This may explain in part the often controversial results in the literature. For example, several studies found that the rate of fat oxidation was higher in both untrained and trained women than men, whereas others found that women use more fat and less carbohydrate than men; still others were unable to report differences between the sexes (25). To avoid those confounding influences, we recently examined lipid metabolism during moderate-intensity endurance exercise in young adult men and women who were matched for fatness, aerobic fitness, and age (26).…”
Section: Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…By doing this the whole complex process of transporting fuels in the blood from other tissues is avoided. Skeletal muscle stores a total of about 8 MJ of energy as glycogen and a further 15 MJ energy as the more energy dense triacyglycerol [2]. Being on the spot such fuels are rapidly available.…”
Section: Choice Of Fuelsmentioning
confidence: 99%
“…Continuing with the theme of fat metabolism, Mittendorfer & Klein (2003) review the factors that control the use of fat and carbohydrate reserves during endurance exercise. They note that while the intensity of exercise determines the increased requirement for energy-yielding metabolism, it is the individual's maximum aerobic capacity that, together with the intensity of the exercise, determines the relative amounts of plasma glucose and fatty acids, muscle glycogen and intramuscular triacylglycerol that will be used.…”
Section: Editorialmentioning
confidence: 99%